Circ-ZDHHC5 Accelerates Esophageal Squamous Cell Carcinoma Progression in vitro via miR-217/ZEB1 Axis - Wang, Qian; Yang, Lili; Fan, Yanxin; Tang, Weiwei; Sun, Handong; Xu, Zhipeng; Zhou, Jian; Zhang, Yanzhou; Zhu, Bin; Cao, Xiufeng (Frontiers in Cell and Developmental Biology, 2020)
Circular RNA (circRNA) exhibits a covalently closed circular conformation and is structurally stable. Nevertheless, the precise effects exerted by circRNA in esophageal squamous cell carcinoma (ESCC) remains uncertain. circRNA was ascertained by a human circRNA array study and was confirmed by the quantification of reverse transcriptase polymerase reactions. A luciferase reporter, fluorescence in situ hybridization experiment was exploited to explore the interaction between circ-ZDHHC5 and miR-217. The function of circ-ZDHHC5 was determined by siRNA-mediated knockout of circ-ZDHHC5 in in vitro proliferation, migration, and invasion. circ-ZDHHC5, rather than linear ZDHHC5 mRNA, rose in the tissues of patients with ESCC, plasma, and ESCC cell lines in comparison with normal controls. Knockdown of circ-ZDHHC5 inhibited tumorigenesis in ESCC cells, and the co-transfection of si-circ-ZDHHC5 and miR-217 mimics further enhanced the above effect. Noticeably, the present study showed that circ-ZDHHC5 was an miR-217 sponge that modulated the expression of zinc finger E-box binding homeobox 1 (ZEB1), further facilitating ESCC tumorigenesis. As revealed by this study, circ-ZDHHC5 can act as a new potential circular biomarker for detecting ESCC. It provides a novel perceptivity for the treatment of ESCC suggesting that circ-ZDHHC5 could impact on ESCC progression by sponging miR-217 with ZEB1.